A phosphatocopid crustacean with appendages from the Lower Cambrian. - Siveter, D; Williams, M; Waloszek, D (2001)
Here we describe a phosphatocopid arthropod with preserved soft anatomy from Lower Cambrian rocks of Shropshire, England, which provides evidence for the occurrence of Crustacea, including Eucrustacea, in the Early Cambrian. The find identifies an important, stratigraphically early source of well-preserved fossils (Konservat-Lagerstätte).